Ultralow-reflection single-layer silicon oxynitride coating method for laser end face and semiconductor laser

By plating a single-layer silicon oxynitride film on the end surface of the laser, the problems of complex multi-layer film process and poor airtightness are solved, and ultra-low reflection and long-term stability of the end surface of the laser are achieved.

CN119710575APending Publication Date: 2025-03-28HENAN SHIJIA PHOTONS TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411817921.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The multi-layer film of the existing laser end surface has complex processes, unstable adhesion between layers, excessive stress, and poor airtightness, which affects the stability of optical performance and the long-term reliability of the laser.

Method used

The ultra-low reflective single-layer silicon oxynitride coating method is used to coat the silicon oxynitride thin film on the end surface of the laser through ion beam sputtering technology, optimize its refractive index and film layer thickness to achieve theoretical zero reflectivity and improve airtightness.

Benefits of technology

It realizes ultra-low reflection of the laser end surface, enhances the environmental adaptability and long-term stability of the laser, and improves output performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710575A_ABST
    Figure CN119710575A_ABST
Patent Text Reader

Abstract

The invention provides an ultralow-reflection single-layer silicon oxynitride coating method for a laser end face and a semiconductor laser, belongs to the technical field of semiconductor lasers, and aims to solve the technical problems of complex process, unstable interlayer adhesion, overlarge stress, poor air tightness and the like of a multilayer film. The method comprises the following steps of: dissociating a semiconductor laser wafer into Bar strips, and plating a silicon oxynitride film on the light-emitting end surfaces of the Bar strips by using an ion beam sputtering technology. The refractive index and the thickness of the silicon oxynitride thin film are theoretically calculated, the theoretical reflectivity of the end face can be reduced to 0% to achieve ultralow reflection, meanwhile, silicon nitride has stronger covalent bonds and is mixed with silicon oxide, so that the thin film has better air tightness than silicon oxide, end face reflection of a laser can be greatly reduced, and the performance of the laser is improved. While the output power of the laser is enhanced, the airtightness of the device is improved, and the reliability of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor lasers, and in particular relates to a chip cavity surface coating. Background Art

[0002] At present, the laser end face usually adopts a multilayer anti-reflection (AR) film to reduce reflection by phase matching between the multilayer films. For example, patent publication number CN 109402606A discloses a method for preparing cavity films with different refractive indices for semiconductor lasers, which includes the following steps: cleaving, clamping, and flattening the semiconductor laser into a chemical vapor deposition device and pumping to a high vacuum to start the film deposition process; heating the substrate and controlling the temperature at 300°C; setting the gas ratio, film thickness and number of layers required for silicon dioxide and silicon nitride respectively, and completing the preparation of the reflective film under computer control; turning the coating fixture back, setting the gas ratio and film thickness required for silicon nitride, and completing the preparation of the transmissive film under computer control. In addition, the existing anti-reflection materials used for laser end faces are mostly silicon oxide (SiO2), aluminum oxide (Al2O3), and silicon (Si). Although they have good optical properties, they are easily corroded in a humid or drastic temperature fluctuation environment due to their poor airtightness, affecting the optical stability of the laser end face, and may cause the laser to fail. To this end, patent publication number CN 114231910A discloses a method for coating chip cavity surfaces and a semiconductor laser, comprising: de-stripping and clamping a wafer to be end-face coated to obtain a bar, and heating the cavity of the bar according to a preset temperature; performing plasma cleaning on the light-emitting cavity surface of the bar to be coated; coating the light-emitting cavity surface of the bar to be coated with a double-layer high-transmittance dielectric film system after the plasma cleaning to coat the light-emitting cavity surface, wherein the double-layer high-transmittance dielectric film system comprises a SiO film layer and a first SiO2 film layer; after coating the light-emitting cavity surface, performing high-energy ion back sputtering on the light-emitting cavity surface according to a preset first time to modify the SiO2 film layer, and coating the SiO2 film layer with a first organic hydrogel film layer by an electron beam, wherein the first organic hydrogel film is in the shape of a convex mirror; performing plasma cleaning on the backlight cavity surface of the bar to be coated. However, multilayer films still have problems such as complex processes, unstable interlayer adhesion, excessive stress, and poor airtightness, especially for indium phosphide (InP) and gallium arsenide (GaAs) substrates. These defects affect the stability of optical performance and the long-term reliability of lasers. Summary of the invention

[0003] In view of the technical problems of multi-layer films such as complex process, unstable interlayer adhesion, excessive stress, and poor airtightness, the present invention proposes an ultra-low reflection single-layer silicon oxynitride coating method for the laser end face and a semiconductor laser. By optimizing the refractive index and film thickness of silicon oxynitride, theoretically zero reflectivity is achieved at a specific operating wavelength, while ensuring high airtightness, so as to enhance the environmental adaptability and long-term stability of the laser.

[0004] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0005] The invention discloses an ultra-low reflection single-layer silicon oxynitride coating method for the laser end face, wherein a semiconductor laser wafer is dissociated into bar strips, and a silicon oxynitride film is coated on the light-emitting end face of the bar strips by using ion beam sputtering technology.

[0006] The refractive index of the silicon oxynitride film is n f Satisfy the following formula:

[0007]

[0008] Where ns is the refractive index of the semiconductor laser substrate at the operating wavelength, and ni is the refractive index of the incident medium.

[0009] The physical thickness d of the silicon oxynitride film satisfies the following relationship:

[0010]

[0011] Where λ is the operating wavelength of the laser.

[0012] The preparation method of the silicon oxynitride film is as follows:

[0013] (1) Place the bar in an ion beam sputtering coating machine and evacuate it to a vacuum. Use auxiliary ion source I to pre-clean the cavity surface;

[0014] (2) After the ion cleaning is completed, an auxiliary ion source II is introduced to grow the silicon oxynitride film.

[0015] The vacuum degree in step (1) is 1.5×10 -7 Torr to 3.0×10 -7 Torr.

[0016] The auxiliary ion source I is Ar gas;

[0017] The conditions for ion pre-cleaning in step (1) are: the gas flow rate of the auxiliary ion source I is 30-60 sccm, the voltage is 60-80 V, the current is 1.5-3 A, and the time is 1-3 min.

[0018] The auxiliary ion source II includes N2 and O2 gases, and the gas flow ratio of N2 to O2 is (2-4):1;

[0019] Preferably, in order to control the refractive index of the silicon oxynitride film within the range of 1.8±0.05, the ratio of N2 to O2 is in the range of 2.8-3.6:1, and in order to control the refractive index of the silicon oxynitride film within the range of 1.85±0.05, the ratio of N2 to O2 is in the range of 3.2-4:1.

[0020] The conditions for the growth of the silicon oxynitride film in step (2) are: the sputtering ion source voltage is 70-90V, the current is 11-13A, the Ar is 12-15sccm, the sputtering rate is 0.3-0.6A / S, the auxiliary ion source II voltage is 60-80V, and the current is 1.5-3A.

[0021] A semiconductor laser, the light-emitting surface of the laser is coated with a silicon oxynitride film.

[0022] Beneficial effects of the present invention: The present invention uses silicon oxynitride as a coating material, and utilizes the excellent optical properties and controllable refractive index of silicon oxynitride. The refractive index and thickness of the film are obtained through theoretical calculations. Through theoretical calculations and design, the theoretical reflectivity of the end face can be reduced to 0% to achieve ultra-low reflection. In addition, because silicon nitride has a stronger covalent bond, it is mixed with silicon oxide and has better air tightness and environmental adaptability than silicon oxide, which improves the reliability of the laser while improving the output of the laser. At the same time, the present invention uses ion beam sputtering coating, and the sputtering ions directly bombard the target material to obtain a dense, low-defect, and low-stress film. Using an auxiliary ion source to emit N + and O + It not only greatly improves the reaction activity and makes the reaction more efficient and stable, but also + and O + The bombardment makes the film layer denser, greatly improving the airtightness and reliability of the laser. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is the spectrum simulation of the semiconductor laser in Example 2.

[0025] Figure 2 for Figure 1 The horizontal and vertical axes correspond to the data.

[0026] Figure 3 This is the refractive index test of the silicon oxynitride film in Example 2.

[0027] Figure 4 This is a calculation diagram of the reflectivity of the silicon oxynitride film in Example 2.

[0028] Figure 5 This is a transmittance diagram of the silicon oxynitride film before and after boiling in Example 2.

[0029] Figure 6 This is a Ripple test diagram of the semiconductor laser in Example 2. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] The operating wavelength of the semiconductor laser is 1550nm, the refractive index of the InP substrate is 3.18 at 1550nm, and the incident medium is air with a refractive index of 1.0.

[0033] The design and production of the film includes the following steps:

[0034] (1)(1) Through the above theoretical calculation, the refractive index nf of the coating material should satisfy the following relationship:

[0035]

[0036] The optical thickness of the film layer needs to be one quarter of the working wavelength, that is, the physical thickness d of the film layer satisfies the following relationship, and the working wavelength is 1550nm:

[0037] It is calculated that the target refractive index of the silicon oxynitride film should be 1.783 and the thickness should be 217.33 nm.

[0038] (2) The semiconductor laser wafer is dissociated into bars with a cavity length of 1000um in air.

[0039] (3) The dissociated Bar strips are fixed on a special fixture for coating and placed into a coating machine (Denton IBS-1040) together with the accompanying InP wafer and the accompanying K9 glass. The pressure is evacuated to 2.0E-7Torr and the substrate cooling water temperature is set to 20°C.

[0040] (4) Then, the auxiliary ion source is turned on to perform ion pre-cleaning on the product. The gas is selected as Ar, the gas flow is set to 50 sccm, the voltage is selected to 75 V, the current is set to 2 A, and the time is 2 min to perform ion cleaning on the product.

[0041] (5) After ion cleaning, thin film growth was carried out. The sputtering ion source voltage was 75 V, the current was 12 A, the Ar was 12.5 sccm, and the sputtering rate was 0.4 A / S. The auxiliary ion source voltage was selected to be 75 V, the current was 2 A, the N2 was 11 sccm, and the O2 was 3.5 sccm. N2 and O2 were fully ionized into N2, O2, and N 2+ , O 2+ 、N + and O + The mixture can be N 2+ and O 2+ and O + and N + The photons are emitted to the substrate to react with Si. The film thickness is confirmed by dual monitoring of the crystal control system and the light control system. The film growth is completed when the thickness reaches the target value.

[0042] Example 2

[0043] The operating wavelength of the semiconductor laser is 1310 nm, the refractive index of the InP substrate is 3.21 at 1310 nm, and the incident medium is air with a refractive index of 1.0.

[0044] The design and production of the film includes the following steps:

[0045] (1) Through the above theoretical calculations, it is calculated that the target refractive index of the silicon oxynitride film should be 1.792 and the thickness should be 182.76 nm.

[0046] (2) The semiconductor laser wafer is dissociated into bars with a cavity length of 1000um in air.

[0047] (3) The dissociated Bar strips are fixed on a special fixture for coating and placed into a coating machine (Denton IBS-1040) together with the accompanying InP wafer and the accompanying K9 glass. The pressure is evacuated to 2.0E-7Torr and the substrate cooling water temperature is set to 20°C.

[0048] (4) Then, the auxiliary ion source is turned on to perform ion pre-cleaning on the product. The gas is selected as Ar, the gas flow is set to 50 sccm, the voltage is selected to 75 V, the current is set to 2 A, and the time is 2 min to perform ion cleaning on the product.

[0049] (5) After ion cleaning, thin film growth was carried out. The sputtering ion source voltage was 75 V, the current was 12 A, the Ar was 12.5 sccm, and the sputtering rate was 0.4 A / S. The auxiliary ion source voltage was selected to be 75 V, the current was 2 A, the N2 was 11.5 sccm, and the O2 was 3.5 sccm. N2 and O2 were fully ionized into N2, O2, and N 2+ , O 2+ 、N + and O + The mixture can be N 2+ and O 2+ and O + and N + The photons are emitted to the substrate to react with Si. The film thickness is confirmed by dual monitoring of the crystal control system and the light control system. The film growth is completed when the thickness reaches the target value.

[0050] Example 3

[0051] The operating wavelength of the semiconductor laser is 1310 nm, the refractive index of the GaAS substrate is 3.40 at 1310 nm, and the incident medium is air with a refractive index of 1.0.

[0052] The design and production of the film includes the following steps:

[0053] (1) Through the above theoretical calculations, it is calculated that the target refractive index of the silicon oxynitride film should be 1.844 and the thickness should be 177.6 nm.

[0054] (2) The semiconductor laser wafer is dissociated into bars with a cavity length of 1000um in air.

[0055] (3) The dissociated Bar strips are fixed on a special fixture for coating and placed into a coating machine (Denton IBS-1040) together with the accompanying InP wafer and the accompanying K9 glass. The pressure is evacuated to 2.0E-7Torr and the substrate cooling water temperature is set to 20°C.

[0056] (4) Then, the auxiliary ion source is turned on to perform ion pre-cleaning on the product. The gas is selected as Ar, the gas flow is set to 50 sccm, the voltage is selected to 75 V, the current is set to 2 A, and the time is 2 min to perform ion cleaning on the product.

[0057] (5) After ion cleaning, thin film growth was carried out. The sputtering ion source voltage was 75 V, the current was 12 A, the Ar was 12.5 sccm, and the sputtering rate was 0.4 A / S. The auxiliary ion source voltage was selected to be 75 V, the current was 2 A, the N2 was 12 sccm, and the O2 was 3.2 sccm. N2 and O2 were fully ionized into N2, O2, and N 2+ , O 2+、N + and O + The mixture can be N 2+ and O 2+ and O + and N + The photons are emitted to the substrate to react with Si. The film thickness is confirmed by dual monitoring of the crystal control system and the light control system. The film growth is completed when the thickness reaches the target value.

[0058] Example 4

[0059] The operating wavelength of the semiconductor laser is 1550nm, the refractive index of the GaAS substrate is 3.37 at 1550nm, and the incident medium is air with a refractive index of 1.0.

[0060] The design and production of the film includes the following steps:

[0061] (1) Through the above theoretical calculations, it is calculated that the target refractive index of the silicon oxynitride film should be 1.835 and the thickness should be 211.17 nm.

[0062] (2) The semiconductor laser wafer is dissociated into bars with a cavity length of 1000um in air.

[0063] (3) The dissociated Bar strips are fixed on a special fixture for coating and placed into a coating machine (Denton IBS-1040) together with the accompanying InP wafer and the accompanying K9 glass. The pressure is evacuated to 2.0E-7Torr and the substrate cooling water temperature is set to 20°C.

[0064] (4) Then, the auxiliary ion source is turned on to perform ion pre-cleaning on the product. The gas is selected as Ar, the gas flow is set to 50 sccm, the voltage is selected to 75 V, the current is set to 2 A, and the time is 2 min to perform ion cleaning on the product.

[0065] (5) After ion cleaning, thin film growth was carried out. The sputtering ion source voltage was 75 V, the current was 12 A, the Ar was 12.5 sccm, and the sputtering rate was 0.4 A / S. The auxiliary ion source voltage was selected to be 75 V, the current was 2 A, the N2 was 11.5 sccm, and the O2 was 3.2 sccm. N2 and O2 were fully ionized into N2, O2, and N 2+ , O 2+ 、N + and O + The mixture can be N 2+ and O 2+ and O + and N +The photons are emitted to the substrate to react with Si. The film thickness is confirmed by dual monitoring of the crystal control system and the light control system. The film growth is completed when the thickness reaches the target value.

[0066] The TFCalc simulation software was used to perform spectrum simulation on the structure designed in Example 2. Figure 1 is the wavelength and reflectivity and the thickness of the SION film, Figure 2 for Figure 1 From the results of extracting image information, it can be seen that when the SION thickness is one-quarter of the optical thickness of the working wavelength, the reflectivity at the central wavelength is 0%.

[0067] The laser prepared in Example 2 was tested. The refraction and thickness of the film were measured by using an ellipsometer to measure the InP film. The results are as follows: Figure 3 As shown, it can be seen that the film thickness and refractive index basically meet the conditions on the InP co-plating film. The refractive index is 1.802 and the thickness is 180.3nm at the 1310nm band. According to the refractive index and thickness measured by the ellipsometer, the reflectivity can be calculated according to the characteristic matrix. Substituting the formula into Excel, the calculation method and results are as follows Figure 4 As shown, it is basically consistent with the simulated structure. The K9 glass piece after the co-plating was boiled in water and its transmittance change was measured using a Carry5000 spectrophotometer. Figure 5 , which can reflect the airtightness of the film, and it can be seen that the film has excellent airtightness. Figure 6 As shown, it can be seen that the ripple fluctuation is not large and it has an excellent anti-reflection effect.

[0068] Characteristic matrix calculation reflectivity process:

[0069]

[0070] Where n0 is the refractive index of the incident medium, n1 is the refractive index of the deposited silicon oxynitride film, and n2 is the refractive index of the substrate. d1 is the physical thickness of the deposited single-layer film.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for coating an ultra-low reflection single-layer silicon oxynitride film on a laser end face, characterized in that: The semiconductor laser wafer is dissociated into Bar strips, and the light-emitting end face of the Bar strips is coated with a silicon oxynitride film using ion beam sputtering technology.

2. The ultra-low reflection single-layer silicon oxynitride coating method for the laser end face according to claim 1, characterized in that: The refractive index of the silicon oxynitride film is n f Satisfy the following formula: Where ns is the refractive index of the semiconductor laser substrate at the operating wavelength, and ni is the refractive index of the incident medium.

3. The ultra-low reflection single-layer silicon oxynitride coating method for laser end face according to claim 2, characterized in that: The physical thickness d of the silicon oxynitride film satisfies the following relationship: Where λ is the operating wavelength of the laser.

4. The method for coating an ultra-low reflection single-layer silicon oxynitride film on a laser end face according to any one of claims 1 to 3, characterized in that: The preparation method of the silicon oxynitride film is as follows: (1) Place the bar in an ion beam sputtering coating machine and evacuate it to a vacuum. Use auxiliary ion source I to pre-clean the cavity surface; (2) After the ion cleaning is completed, an auxiliary ion source II is introduced to grow the silicon oxynitride film.

5. The ultra-low reflection single-layer silicon oxynitride coating method for laser end face according to claim 4, characterized in that: The vacuum degree in step (1) is 1.5×10 -7 Torr to 3.0×10 -7 Torr.

6. The ultra-low reflection single-layer silicon oxynitride coating method for laser end face according to claim 5, characterized in that: The auxiliary ion source I is Ar gas.

7. The ultra-low reflection single-layer silicon oxynitride coating method for laser end face according to claim 6, characterized in that: The conditions for ion pre-cleaning in step (1) are: the gas flow rate of the auxiliary ion source I is 30-60 sccm, the voltage is 60-80 V, the current is 1.5-3 A, and the time is 1-3 min.

8. The method for coating an ultra-low reflection single-layer silicon oxynitride film on a laser end face according to claim 4, characterized in that: The auxiliary ion source II includes N2 and O2 gases, and the gas flow ratio of N2 to O2 gases is (2-4):

1.

9. The ultra-low reflection single-layer silicon oxynitride coating method for laser end face according to claim 8, characterized in that: The conditions for the growth of the silicon oxynitride film in step (2) are: the sputtering ion source voltage is 70-90V, the current is 11-13A, the Ar is 12-15sccm, the sputtering rate is 0.3-0.6A / S, the auxiliary ion source II voltage is 60-80V, the current is 1.5-3A, and the gas flow rate of the auxiliary ion source II is 10-20sccm.

10. A semiconductor laser, characterized in that: A chip cavity surface prepared by the ultra-low reflection single-layer silicon oxynitride coating method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing cavity facet film with different refractive indexes of semiconductor laser

    CN109402606A

  • Chip cavity surface coating method and semiconductor laser

    CN114231910A